PENGARUH PEMBANGUNAN INFRASTRUKTUR TERHADAP PERTUMBUHAN EKONOMI KABUPATEN GORONTALO UTARA - Andi Mardiana; Azhar Habu (MUTAWAZIN (Jurnal Ekonomi Syariah), 2022)
Development is one of the most important factors in increasing economic growth and one of the drivers of the rate of economic growth in an area is the existence of infrastructure development. Because infrastructure development is a mobility that can bring changes in the level of welfare of the population. This study aims to find out more about the influence of infrastructure development on the economic growth of North Gorontalo Regency in the 20142017 period. The research method used is a quantitative research method. To be able to make measurements, each phenomenon is translated into several problem components, variables and indicators. The type of data in this study is secondary data. The results show that the results of descriptive statistical analysis on the variables of economic growth, road infrastructure development, education infrastructure development, agricultural infrastructure development and health infrastructure development when compared to the average, the standard deviation is much smaller so that the data on the infrastructure can be justified by the value. average. ABSTRAK